PEMBUATAN DAN PENGUJIAN PROTOTIPE DESALINASI BERTENAGA SURYA YANG DIKOMBINASIKAN DENGAN LAMPU ULTRAVIOLET DAN SISTEM OTOMATIS BERBASIS MIKROKONTROLER - Rosyad, Muhammad Sabilul; Marhaendrajaya, Indras; Sutanto, Heri (BERKALA FISIKA, 2024)
The lack of availability of clean water quantitatively is due to 97% of the water on earth is sea water, with a salt content of seawater of around 35000 mg/L causing the water to be unable to be used directly without prior treatment. One of the efforts that can be done to overcome the clean water crisis is through seawater desalination to produce water with low salinity. Several desalination methods that have existed are MSF (Multi Stage Flash Distillation) and Reverse Osmosis. But both of these methods have a high cost. Therefore, we need a method that is cheaper and easier to implement such as distillation. In this research, seawater desalination process uses the distillation method combined with a vacuum pump, electric stove and ultraviolet lamp. The use of a vacuum pump in the distillation system can speed up the evaporation process of seawater. Ultraviolet lamps function to degrade heavy metal pollutants and remove harmful bacteria. To maximize the performance of the tool, an electric stove with an automation system is added with solar panels as its energy source. Analysis of the tests carried out included the construction of the prototype, characterization and calibration of the LDR (Light Dependent Resistor) sensor and Arduino UNO microcontroller, total energy production and use, water production speed, and water quality. The results obtained include a prototype of seawater desalination. The characterization and calibration of the sensor in the automated system that the LDR sensor is running accurately, together with the Arduino UNO microcontroller, the LDR sensor can be an automation system that can make the prototype turn on and off automatically. The use of ultraviolet lamps shows that ultraviolet lamps have a photon energy of 3.0 eV and are able to work in visible light. The use of solar panels as an energy source can make an energy efficient prototype. This tool technology can increase water productivity up to 2 times and water quality shows a decrease in several pollutant parameters in distilled water including TDS (Total Dissolve Solid) of 99.7%, electrical conductivity of 99.987%, salinity of 99.93% , total coliform was 100%, and heavy metals Pb was 82.47%, Cd was 60.33%, Cu was 100%, Fe was 96.1%, Cr was 90.33%, and Zn was 98.9% , and the pH of seawater became neutral from 7.5 to 6.9. This prototype technology has the potential to be applied to the community.